Addressing Regulatory Risks in Fintech through Decentralized Technologies - Fahrudin, Rifqi; Dwi Yulian, Firdaus; Yadi Fauzi, Ahmad; Wilson, Ashley; Kuusk, Taavi (APTISI Transactions on Management (ATM), 2024)
The fintech industry, characterized by rapid innovation and disruption of traditional financial services, faces significant regulatory challenges that can hinder its growth and sustainability. Managing these regulatory risks is crucial to ensuring compliance and maintaining trust within the industry. Decentralized technologies, particularly blockchain, have emerged as potential solutions for enhancing regulatory compliance through increased transparency, security, and automation. This study aims to analyze the role of decentralized technologies in addressing regulatory risks in the fintech sector. Utilizing the SmartPLS method for data analysis, the research examines the relationships between decentralized technology adoption, compliance automation, and regulatory risk mitigation. The findings reveal that decentralized technologies significantly reduce regulatory risks by automating compliance processes and enhancing transparency. These insights offer valuable implications for fintech companies and regulators, suggesting that the integration of decentralized technologies can be a strategic approach to managing regulatory challenges in the industry.